2019
DOI: 10.4314/tjpr.v17i12.16
|View full text |Cite
|
Sign up to set email alerts
|

Tangeritin attenuates oxidative stress, apoptosis and inflammation in cadmium-induced cardiotoxicity in rats by activating Nrf2 signaling pathway

Abstract: Purpose: To determine the effect of tangeritin on cadmium-induced cardiotoxicity in rats. Methods: Cardiotoxicity was induced by intra-gastric administration of 5 mg/kg cadmium chloride to rats, once daily for 4 weeks. The animals were treated with tangeritin at 10 and 20 mg/kg p.o. 60 min before the administration of cadmium, for 4 weeks. Thereafter, the concentrations of cadmium in serum and cardiac tissue were determined, and markers of cardiac function, antioxidant enzyme activities and levels of pro-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…NRF2 signaling is known to be involved in oxidative stress [21,22], and activation of this signaling pathway alleviates cisplatin-induced nephrotoxicity [7,9]. To study the underlying mechanism of Z-lig protection against cisplatin nephrotoxicity, we investigated activation of NRF2 signaling in cisplatin-treated HK-2 cells and showed that Z-lig activated the NRF2/HO-1 signaling pathway, a result consistent with previous studies [23,24].…”
Section: Discussionsupporting
confidence: 82%
“…NRF2 signaling is known to be involved in oxidative stress [21,22], and activation of this signaling pathway alleviates cisplatin-induced nephrotoxicity [7,9]. To study the underlying mechanism of Z-lig protection against cisplatin nephrotoxicity, we investigated activation of NRF2 signaling in cisplatin-treated HK-2 cells and showed that Z-lig activated the NRF2/HO-1 signaling pathway, a result consistent with previous studies [23,24].…”
Section: Discussionsupporting
confidence: 82%
“…For instance, formononetin displayed significant hypoglycemic activity [15]; beta-sitosterol showed therapeutic effects on DM, anti-oxidation, and reducing blood lipids [16], and quercetin played an important role in treating obesity and DM [17,18]. In addition, the ononin, genistein, daidzein, daidzin, and tangeritin were detected in the metabolites of Pueraria lobata by LC/MS, and their certain pharmacological effects in anti-inflammatory, anti-diabetic and anti-tumor aspects were reported [19][20][21]. For example, ononin displayed effects on LPS-induced inflammatory response, which may be associated with NF-κB and MAPK pathways [22]; genistein showed the pharmacological effects on breast tumor, prostate tumor, atherosclerosis, and DM [23][24][25].…”
Section: Active Ingredients From Pueraria Lobatamentioning
confidence: 99%
“…The rats were exposed to the respective treatment as mentioned in the groups for 28 d. On the 28 th d, rats fasted for 24 h and blood was drawn by cardiac puncture under ether anesthesia for various biochemical estimations. The animals were sacrificed by cervical decapitation and the heart was dissected out, immediately rinsed in ice-cold saline, and stored for further biochemical and histopathological analysis [15,16] .…”
Section: Experimental Designmentioning
confidence: 99%